Stakeholders’ engagement for improved health outcomes: a research brief to design a tool for better communication and participation - Pellegrini, Giuseppe; Lovati, Chiara (Frontiers in Public Health, 2025)
Technological progress in healthcare is creating a complexity of novelties, from new roles and challenges, to new concerns about inclusivity, equity and data privacy. Communication among healthcare actors becomes a very important factor for adaptation and allows for the improvement of medical research and treatment. Active patient involvement and stakeholder engagement in health research become essential to better information and diagnostic management and communication in a framework of ever-expanding resources defined by the rise of artificial intelligence and other technologies. At the intersection of healthcare, technology and citizenship, the EU-funded Hereditary project plans to facilitate trough Health Social Laboratories (HSL) a multi-level dialog between stakeholders, improving its health outcomes while accounting for the challenges and risks of communication in participatory approaches. This study aims to understand the main issues to address in developing an effective stakeholder collaborative relationship with a focus on communication in a technology-driven context such as the Hereditary project and its health information integration processes. It specifically describes the findings of a literature review, an exploratory context analysis carried out through interviews with 9 key informants from four research partner locations (four interviewees in Italy, two in the Netherlands, one in Spain, and two in the United States), and the transformation of these findings into a prospective laboratory methodology. Our approach aims to highlight the importance of including diverse perspectives in shaping healthcare communication innovation. Through a participative model, researchers can navigate complex ethical and practical healthcare communication challenges more effectively, and foster solutions that are in alignment with stakeholders’ needs.